Beyond fragmentation : cross-fertilization, cooperation and competition among international courts and tribunals / edited by Chiara Giorgetti, University of Richmond, Mark Pollack, Temple University. - Giorgetti, Chiara; Pollack, Mark A., 1966- (Studies on international courts and tribunals., 2022)
Beyond Fragmentation assembles a unique team of expert practitioners and leading scholars to explore and advance the study of cross-fertilization among international courts and tribunals. Using an inter-disciplinary and multi-method approach, contributors analyse how international courts and tribunals interact and why it matters in practice. After a thorough review of prior assessments of cross-fertilization and fragmentation, the editors offer a new take on competition and cooperation across courts and tribunals, exploring both substantive and procedural elements as well as the diverse agents of cross fertilization. Contributors engage with procedural issues, identifying a "procedural cross-fertilization pull" and why and how procedure is converging in international courts and tribunals. Case studies on the convergence in the law of the sea and at the European Court of Human Rights provide contrasting experiences of substantive cross-fertilization. The volume also identifies a variety of agents of cross-fertilization, including judges, litigants, counsel, and international organizations.